2006
DOI: 10.1242/jeb.02069
|View full text |Cite
|
Sign up to set email alerts
|

Taste discrimination in conditioned taste aversion of the pond snailLymnaea stagnalis

Abstract: Conditioned taste aversion (CTA) in the pond snailLymnaea stagnalis has been widely used as a model for gaining an understanding of the molecular and behavioral mechanisms underlying learning and memory. At the behavioral level, however, it is still unclear how taste discrimination and CTA interact. We thus examined how CTA to one taste affected the feeding response induced by another appetitive food stimulus. We first demonstrated that snails have the capacity to recognize sucrose and carrot juice as distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 46 publications
(36 reference statements)
2
44
0
Order By: Relevance
“…Consistent with this hypothesis are the data showing that altered gene activity and new protein synthesis must occur in these and other neurons if LTM is to form following the CTA procedure Hatakeyama et al, 2004b;Hatakeyama et al, 2006;Azami et al, 2006;Wagatsuma et al, 2006). In addition, our recent findings showed that snails are both able to discriminate different tastes and continue to eat other foods following the CTA procedure (Sugai et al, 2006).…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…Consistent with this hypothesis are the data showing that altered gene activity and new protein synthesis must occur in these and other neurons if LTM is to form following the CTA procedure Hatakeyama et al, 2004b;Hatakeyama et al, 2006;Azami et al, 2006;Wagatsuma et al, 2006). In addition, our recent findings showed that snails are both able to discriminate different tastes and continue to eat other foods following the CTA procedure (Sugai et al, 2006).…”
Section: Introductionsupporting
confidence: 65%
“…The CS used was either 5·ml of 10·mmol·l -1 sucrose solution (CS1) or 5·ml of 0.3% carrot juice solution (CS2), whereas the US was 5·ml of 10·mmol·l -1 KCl. Either CS elicits a reliable feeding response (number of bites·min -1 ) from snails deprived of food for 1·day, whereas the US reliably causes the snails to stop their feeding behavior (Sugai et al, 2006). Higher concentrations of KCl cause snails to withdraw into their shells for a long period (Kojima et al, 1996) and so were not used in our studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we look at the ability of Lymnaea to learn and remember for many days not to respond to a food substance that normally elicits a feeding response. This is referred to as conditioned taste aversion (CTA) (Ito et al, , 2012Kawai et al, 2004;Sugai et al, 2006;Takigami et al, 2014). To produce a CTA, an appetitive stimulus, such as sucrose [the conditioned stimulus (CS)], is repeatedly paired with an aversive stimulus, such as an electric shock [the unconditioned stimulus (US)] Ito et al, 2015).…”
Section: Introductionmentioning
confidence: 99%